Complications of bariatric surgery three procedures and ten years later - Osorno Carbonell, Giovanna; Cisneros Arias, Francisco de Jesus (International Journal of Research in Medical Sciences, 2024)
Two types of metabolic surgeries are currently most used: vertical tubular gastrectomy and Roux-en-Y gastric bypass. Complications can be early and late. There are 3 types of revision surgeries: corrective and reversal surgeries, to restore normal anatomy, and conversion surgeries, which consist of changing to another bariatric procedure for complications or inadequate response. We report the case of a 47-year-old female who, 10 years prior to her admission, underwent vertical gastrectomy, presenting symptoms refractory to PPI treatment one year after surgery, so conversion to gastric bypass was performed. Seven years later, she came to us due to stenosis of the gastrojejunal anastomosis as well as marginal ulcer. She underwent a total of 4 dilations in 6 months, with no improvement in symptoms. We decided to perform gastrojejunal anastomosis remodeling. She presents an adequate post-surgical evolution. It is essential to know the complications derived from bariatric surgery and the management options we have, as well as to carry out long-term follow-up, to guarantee not only the desired weight loss or improvement in comorbidities, but also an adequate quality of life in the patient.